Interventions that cross the elderly - Atzori, Elisabetta; Di Venosa, Sara; Nicolini, Matteo; Scala, Vincenzo F.; Tanga, Claudia; Vanacore, Roberto (Quaderni di Psicologia Clinica, 2023)
Five cases of intervention within different operational contexts and aimed at recipients who are not primarily elderly subjects are presented and commented on. However, the elders appear in the course of these experiences and it is understood that paying attention to them is not only a necessity, but becomes an important resource for proceeding in the intervention relationship.
Keywords: social and health services for families; elders; clinical psychological intervention; grandparents; nanny.